Xenomyrothecium tongaense PTS8: a rare endophyte of Polianthes tuberosa with salient antagonism against multidrug-resistant pathogens - Sundar, Ranjitha Dhevi V.; Arunachalam, Sathiavelu (Frontiers in Microbiology, 2024)
Introduction Endophytes refer to microorganisms residing within the endosphere of plants, particularly perennials, without inflicting noticeable injury or inducing obvious morphological variations to their host plant or host organism. Endophytic fungi, although often overlooked microorganisms, have garnered interest due to their significant biological diversity and ability to produce novel pharmacological substances. Methods In this study, fourteen endophytic fungi retrieved were from the stem of the perennial plant Polianthes tuberosa of the Asparagaceae family. These fungal crude metabolites were tested for antagonistic susceptibility to Multi-Drug Resistant (MDR) pathogens using agar well diffusion, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) assays. The chequerboard test was used to assess the synergistic impact of active extract. Results and discussion In early antibacterial screening using the Agar plug diffusion test, three of fourteen endophytes demonstrated antagonism against Methicillin-resistant Staphylococcus aureus (MRSA) and Vancomycin-resistant Enterococcus (VRE). Three isolates were grown in liquid medium and their secondary metabolites were recovered using various organic solvents. Eight extracts from three endophytic fungi displayed antagonism against one or more human pathogens with diameters ranging from 11 to 24 mm. The highest antagonistic effect was obtained in ethyl acetate extract for PTS8 isolate against two MRSA (ATCC 43300, 700699) with 20 ± 0.27 and 22 ± 0.47 mm zones of inhibition, respectively, among different solvent extracts. The extract had MICs of 3.12 ± 0.05 and 1.56 ± 0.05 μg/mL, and MBCs of 50 ± 0.01 and 12.5 ± 0.04 μg/mL, respectively. Antagonism against VRE was 18 ± 0.23 mm Zone of Inhibition (ZOI) with MIC and MBC of 6.25 ± 0.25 and 25 ± 0.01 μg/mL. When ethyl acetate extract was coupled with antibiotics, the chequerboard assay demonstrated a synergistic impact against MDR bacteria. In an antioxidant test, it had an inhibitory impact of 87 ± 0.5% and 88.5 ± 0.5% in 2,2-Diphenyl-1-Picrylhydrazyl and reducing power assay, respectively, at 150 μg/mL concentration. PTS8 was identified as a Xenomyrothecium tongaense strain by 18S rRNA internal transcribed spacer (ITS) sequencing. To our insight, it is the foremost study to demonstrate the presence of an X. tongaense endophyte in the stem of P. tuberosa and the first report to study the antibacterial efficacy of X. tongaense which might serve as a powerful antibacterial source against antibiotic-resistant human infections.